Discourse on Prohibition of Marriage With the Colleagues for Public Servants: Diskursus Larangan Nikah dengan Rekan Sekantor bagi Aparatur Sipil Negara - Muh. Afdal Yanuar (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
After the Constitutional Court Decision Number 13/PUU-XV/2017, the labor regime which provided possibility of prohibiting workers for having marital bond with the colleagues, has been distorted to become a permissibility, after annulling Article 153. (1). f the Labor Law. In the scope of State Civil Apparatus, there are several reasonable arguments that the Decision can be extended to them, which is: (a) there is similarity between State Civil Apparatus and labors in the matter of employment relationship. where State Civil Apparatus is an employee which employed by the government, while the labor by the company; and (b) the State Civil Apparatus law doesn’t prohibit them from having a marital bond with the colleagues. Based on that, the restriction on the right to establish a family and to get fair and proper treatment by forcing the prohibition of the marital bond with the colleagues through the internal office regulations shall not be justified.